Characterization of a Commercial Whey Protein Hydrolysate and Its Use as a Binding Agent in the Whey Protein Isolate Agglomeration Process - B. Zaitoun; N. Palmer; J. Amamcharla (Kansas Agricultural Experiment Station Research Reports, 2020)
Soy lecithin is a commonly used binder in agglomerating dairy powders. Due to the increase in consumer awareness on “clean label” and also to increase the shelf-life of agglomerated whey protein isolate (WPI), the demand of lecithin-free agglomerated WPI has increased. In this work, whey protein hydrolysate (WPH) was utilized as a binder to facilitate the agglomeration of WPI. The first objective was to characterize the chemical properties of three lots of WPH obtained from a commercial manufacturer. The degree of hydrolysis (DH) of WPH was 13.82–15.35% and not significantly (P>0.05) different between the lots. It was observed from the high-performance liquid chromatography (HPLC) that the major whey proteins were completely hydrolyzed indicating a consistent hydrolysis between the lots. The second objective of the study was to evaluate the effectiveness of WPH as a binder in WPI wet agglomeration. After the agglomeration was performed, agglomerated WPI samples were stored at 25°C (77°F) and analyzed for moisture, water activity, relative dissolution index (RDI), and emulsifying capacity. Moisture content (MC) of agglomerated samples was in the range of 3–15%, whereas water activity was within the range of 0.08–0.80. There was a significant (P<0.05) difference in both moisture content and water activity among the treatments. Per-wet mass, flow rate, and the WPH concentration had significant (P<0.05) effects on the MC. Moreover, all interactions among the main effects also had a significant (P<0.05) effect on MC. High MC and water activity were observed for the treatments with higher pre-wet volume and higher flow rate and also resulted in clumping of the powders. The treatment that had 60 g of pre-wet, 20% WPH concentration, and 5.6 mL/min flow rate combination had the highest RDI among all the samples. In conclusion, WPH can be used as a potential alternative to soy lecithin in WPI wet agglomeration.
Keywords: agglomeration; whey protein; hydrolysate